Transformation from the ground: Adaptation pioneers as agents of change through climate-resilient agriculture - Habermann, Birgit; Gichuki, Leah; Worku, Tigist; Kiptoo, Emmaculate; Crane, Todd A.; DuttaGupta, Tanaya (International Livestock Research Institute, 2024)
Adaptation to climate change is neither optional nor hypothetical. It is no longer something that we plan for in the future. The time is here and now. Smallholder farmers and herders the world over know this through their own lived experiences. Acknowledging this fact through transdisciplinary collaboration with a focus on farmer-led innovation (F-LI) for adaptation is a rising priority in the domain of climate change adaptation. However, it is often unclear how exactly to implement this in practice. While much adaptation work starts with analyzing problems and building out from that anchor, there is much to be gained in starting with climate solutions that are already effectively embedded within livelihoods and communities.